2018
DOI: 10.15625/2525-2518/56/1/9732
|View full text |Cite
|
Sign up to set email alerts
|

NUCLEOTIDE DIVERSITY OF 15 CONIFER SPECIES IN VIETNAM’ S CENTRAL HIGHLANDS BASED ON THE ANALYSIS OF ITS, trnH-psbA, matK, trnL AND rpoC1 GENE REGIONS

Abstract: Abstract. In this study, five DNA sequences from ITS, trnH-psbA, matK, trnL and rpoC1 gene regions were used to explore relationships of 15 conifer species in Highland of Vietnam. All target gene segments have been cloned at size as predicted by the theory for all 15 species of conifers. Nucleotide-level change of 15 coniferous species in five gene regions showed from the highest to the lowest as follows: the ITS gene region (0.428), the trnH-psbA region (0.378), the trnL (0.354), the matK gene (0.192) and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Kress et al (2015) studied 296 woody species in Panama and found that the species identification rate through matK + rbcL was high, i.e., 98%. Phong et al (2018) suggested the use of three gene regions, i.e., matK, trnL and rpoC1 as a barcode for the identification of fifteen conifer species in the Central Highland of Vietnam. In our study, the core barcode matK region covered the identification of all thirty-three local conifer species (Figure 1), while the rbcL regions were weak in some species (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kress et al (2015) studied 296 woody species in Panama and found that the species identification rate through matK + rbcL was high, i.e., 98%. Phong et al (2018) suggested the use of three gene regions, i.e., matK, trnL and rpoC1 as a barcode for the identification of fifteen conifer species in the Central Highland of Vietnam. In our study, the core barcode matK region covered the identification of all thirty-three local conifer species (Figure 1), while the rbcL regions were weak in some species (Figure 2).…”
Section: Discussionmentioning
confidence: 99%
“…This 2-locus barcode can identify species and will contribute to the discovery of new species (Burgess et al 2011;de Vere et al 2012;Kress et al 2015). Different researchers have studied the identity, genetic variation and verified the taxonomic status of conifer species at the molecular level (de Vere et al 2012;Zheng et al 2016;Asaf et al 2018;Phong et al 2018;Kang et al 2019;). However, fewer researchers have studied conifers in Vietnam.…”
mentioning
confidence: 99%